Group 1 and group 2 hemagglutinin stalk antibody response according to age - Sánchez-de Prada, Laura; Sanz-Muñoz, Iván; Sun, Weina; Palese, Peter; Ortiz de Lejarazu, Raúl; Eiros, José María; García-Sastre, Adolfo; Aydillo, Teresa (Frontiers in Immunology, 2023)
Objective Antibodies elicited by seasonal influenza vaccines mainly target the head of hemagglutinin (HA). However, antibodies against the stalk domain are cross-reactive and have been proven to play a role in reducing influenza disease severity. We investigated the induction of HA stalk-specific antibodies after seasonal influenza vaccination, considering the age of the cohorts. Methods A total of 166 individuals were recruited during the 2018 influenza vaccine campaign (IVC) and divided into groups: <50 (n = 14), 50–64 (n = 34), 65–79 (n = 61), and ≥80 (n = 57) years old. Stalk-specific antibodies were quantified by ELISA at day 0 and day 28 using recombinant viruses (cH6/1 and cH14/3) containing an HA head domain (H6 or H14) from wild bird origin with a stalk domain from human H1 or H3, respectively. The geometric mean titer (GMT) and the fold rise (GMFR) were calculated, and differences were assessed using ANOVA adjusted by the false discovery rate (FDR) and the Wilcoxon tests (p <0.05). Results All age groups elicited some level of increase in anti-stalk antibodies after receiving the influenza vaccine, except for the ≥80-year-old cohort. Additionally, <65-year-old vaccinees had higher group 1 antibody titers versus group 2 before and after vaccination. Similarly, vaccinees within the <50-year-old group showed a higher increase in anti-stalk antibody titers when compared to older individuals (≥80 years old), especially for group 1 anti-stalk antibodies. Conclusion Seasonal influenza vaccines can the induction of cross-reactive anti-stalk antibodies against group 1 and group 2 HAs. However, low responses were observed in older groups, highlighting the impact of immunosenescence in adequate humoral immune responses.